Trapping and proliferation of target cells on C60 fullerene nano fibres - Seiki Iwai; Shunji Kurosu; Hideki Sasaki; Kazunori Kato; Toru Maekawa (Heliyon, 2017)
The ratio of the surface area to the volume of materials increases in inverse proportion to their size and therefore the surface area of nanostructures and nanomaterials is extremely large compared to that of macroscopic materials of the same volume, thanks to which it is supposed that chemical and biochemical reactions may be greatly enhanced and target molecules and cells may be efficiently trapped on the surface of nanomaterials. It is well known that C60 molecules are stable both physically and chemically and the affinity of C60 molecules with biomolecules is rather high. Here, we synthesise fibres composed of C60 and sulphur and immobilise the surface of the fibres with the primary antibody; i.e., epithelial cell adhesion molecules (anti-EpCAM), to trap target cells. The primary antibody is evenly immobilised on the fibres confirmed by a fluorescent secondary antibody attached to the primary one and then TE2 esophageal and DLD-1 colon cancer cells are successfully trapped by the primary antibody immobilised on the fibres thanks to its high affinity with TE2 and DLD-1 cells, whereas few IM9 B lymphoblast cells are captured on the fibres since the affinity of the primary antibody with IM9 cells is extremely low. Furthermore, those cells trapped by the primary antibody immobilised on the fibres proliferate faster than native cells thanks to the primary antibody acting as a growth factor. The present result suggests that different types of cells can be trapped and grown on nano fibres by immobilising appropriate antibody molecules on the surface of the fibres. Even an extremely small number of cells in sample fluids may be analysed and characterised for the detection of diseases such as cancer in the early stage by trapping and proliferating target cells on the fibres.